Barbalien: red planet ebook - Brombal, Tate (Barbalien: Red Planet (2020)., 2021)
A groundbreaking new sci-fi action series in the world of the Eisner Award-winning Black Hammer universe, about prejudice, honor, and identity.Mark Markz has found his place on Earth as both a decorated police officer and as the beloved superhero, Barbalien. But in the midst of the AIDS crisis, hatred from all sides makes balancing these identities seem impossible--especially when a Martian enemy from the past hunts him down to take him back, dead or alive.Collects Barbalien: Red Planet #1-#5. Author: Jeff Lemire, Tate Brombal. Illustrator: Gabriel Hernandez Walta.